EFEK SALEP CAMPURAN BIJI KELENGKENG (DIMOCARPUS LONGAN LOUR), MINYAK ZAITUN DAN LILIN LEBAH TERHADAP PENYEMBUHAN LUKA BAKAR PADA TIKUS PUTIH JANTAN GALUR WISTAR - LUKMAN HAKIM ROMA MORA SIREGAR; ILHAM HARIAJI (LP2MTBM MAKARIOZ, 2021)
Burns is defined as type of injury to skin and cause the loss of barriers to fight infection. If not treated properly, burns can belife-threatening. Longan seeds, olive oil and beeswax, which have potential to help the healing process of burns. To know theeffect of ointment mixture of longan seeds, olive oil and beeswax to healing burns in white male wistar rats. This research isan experimental posttest-only control-group design with a total sampling of 15 rats, and divided into two groups; givenointment (S) and without ointment (TS). Data will be analyzed by T-Independent and Mann-Whitney test. Average of thereduction diameter (S=2.64%,TS=8.28%), percentage of healings (S=88.62%, TS=65.42%), and time of healing (S=16days,TS=23 days). The analysis of the data obtained ρ=0.00. There are significant differences in the reduction in burnsdiameter, percentage of burns healing and time of burns healing in two groups. Group S have a better healing effect onburns than group TS.